2008
DOI: 10.1098/rstb.2008.0203
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of the amblyopic visual system

Abstract: Experience-dependent plasticity is closely linked with the development of sensory function; however, there is also growing evidence for plasticity in the adult visual system. This review re-examines the notion of a sensitive period for the treatment of amblyopia in the light of recent experimental and clinical evidence for neural plasticity. One recently proposed method for improving the effectiveness and efficiency of treatment that has received considerable attention is 'perceptual learning'. Specifically, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 77 publications
3
116
0
Order By: Relevance
“…82 Only in a few tasks (Vernier acuity, contrast sensitivity and detection) did training lead, at least in some subjects, to a generalization of beneficial effects to other degraded visual functions, such as VA and stereoacuity. 81 Interestingly, it has been suggested that the balance between excitation and inhibition is also impaired during development in amblyopic human subjects and that cortical overinhibition could underlie the degradation of spatial vision abilities. [83][84][85][86][87] The study of experimental models of amblyopia has the advantage of enabling researchers to uncover new molecular mechanisms underlying the therapeutic value of the used procedures.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…82 Only in a few tasks (Vernier acuity, contrast sensitivity and detection) did training lead, at least in some subjects, to a generalization of beneficial effects to other degraded visual functions, such as VA and stereoacuity. 81 Interestingly, it has been suggested that the balance between excitation and inhibition is also impaired during development in amblyopic human subjects and that cortical overinhibition could underlie the degradation of spatial vision abilities. [83][84][85][86][87] The study of experimental models of amblyopia has the advantage of enabling researchers to uncover new molecular mechanisms underlying the therapeutic value of the used procedures.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Strikingly, an increasing number of clinical studies have reported that repetitive visual training based on sensory enrichment procedures may represent a very useful approach for the treatment of amblyopia, providing substantial improvement in a variety of visual tasks [76][77][78][79] (for a review, see Polat 80 and Levi and Li 81 ). One caveat to the therapeutic value of these visual practice procedures, however, is the narrow specificity of achievable improvement, which is typically limited to the selected trained stimulus, condition or task.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Whereas the earliest attempts, such as training on vernier alignment (Levi & Polat 1996), showed only limited generalization beyond the specific trained target orientation, later attempts to ameliorate the deficient spatial interactions in low-level vision in amblyopia by perceptual training led to improvement of other aspects of vision such as Snellen acuity, counting and contrast sensitivity (e.g. Polat et al 2004;Levi 2005;Zhou et al 2006;Li et al 2007; see also Levi & Li 2009). …”
Section: The Present and Potential Future Impact Of Work On Animal Momentioning
confidence: 99%
“…This is also the case with strabismus (a condition in which the eyes are not properly aligned with each other. It typically involves a lack of coordination between the extraocular muscles that prevents the gaze of each eye being brought to the same point in space and preventing proper binocular vision, which may adversely affect depth perception), which if not corrected by 7 years of age leads to a severe impairment (Levi & Li, 2009). Therefore, periods in the maturation of the visual system circuitry appear to constitute critical periods of vulnerability, epochs in the experiential input are required for normal development of the specific circuits and their functional capacity, without which the potential for development of those functional capacities is lost forever (Morishita & Hensch, 2008).…”
Section: Experience-dependent Developmental Plasticitymentioning
confidence: 99%